2018
DOI: 10.1021/acsnano.8b04222
|View full text |Cite
|
Sign up to set email alerts
|

Protein Nanostructures Produce Self-Adjusting Hyperpolarized Magnetic Resonance Imaging Contrast through Physical Gas Partitioning

Abstract: Signal amplification strategies are critical for overcoming the intrinsically poor sensitivity of nuclear magnetic resonance (NMR) reporters in noninvasive molecular detection. A mechanism widely used for signal enhancement is chemical exchange saturation transfer (CEST) of nuclei between a dilute sensing pool and an abundant detection pool. However, the dependence of CEST amplification on the relative size of these spin pools confounds quantitative molecular detection with a larger detection pool typically ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 42 publications
(105 reference statements)
2
30
0
Order By: Relevance
“…They are composed of two dominant protein subunits termed gas vesicle protein A (GvpA) and gas vesicle protein C (GvpC) 6 . Due to the presence of their air-filled internal core, GVs can respond to ultrasound waves and produce hyperpolarized magnetic resonance contrast for imaging 7,8 . Moreover, as a genetically encoded nanostructure new ligands can be introduced into the surface gvpC protein through genetic recombinant approaches 9 .…”
mentioning
confidence: 99%
“…They are composed of two dominant protein subunits termed gas vesicle protein A (GvpA) and gas vesicle protein C (GvpC) 6 . Due to the presence of their air-filled internal core, GVs can respond to ultrasound waves and produce hyperpolarized magnetic resonance contrast for imaging 7,8 . Moreover, as a genetically encoded nanostructure new ligands can be introduced into the surface gvpC protein through genetic recombinant approaches 9 .…”
mentioning
confidence: 99%
“…Cryptophanes with their tailored cavity sizes have thus been used in many sensor designs as starting material for coupling with binding motifs for different biological targets [ 15 , 127 , 128 , 129 , 130 , 131 ]. Further development of the HyperCEST approach, however, showed that there are other hosts with better Xe exchange dynamics [ 123 , 124 , 132 , 133 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…In nature, photosynthetic bacteria and archaea produce intracellular GVs as a means to achieve cellular buoyancy 18 . Recently it was discovered that GVs' gas-filled interiors allow them to serve as contrast agents for high-frequency diagnostic ultrasound and MRI 13,14,16,[19][20][21][22] . In addition, it was shown that engineered multi-gene clusters encoding GVs can be heterologously expressed in Escherichia coli and Salmonella typhimurium, two frequently used bacterial chasses for the development of cellbased diagnostic and therapeutic agents 15 .…”
Section: Introductionmentioning
confidence: 99%